Food Security: Challenges for a sustainable world - Gomes ES; Nina IP; Rego LF; Nunes R (2012)
On June 12, 2012, the Food Security session was held during the Forum on Science, Technology and Innovation for Sustainable Development at the Pontifical Catholic University of Rio de Janeiro, with co-conveners Prof. Thomas Rosswall, Chair, CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), and Dr. Lindiwe MajeleSibanda, CEO, Food, Agriculture and Natural Resources Policy Analysis Network (FANRPAN), South Africa. The invited forum lecturers called attention to a number of challenges that need to be tackled in order to achieve food security worldwide, such as climate change, loss of arable land, wars and social/cultural conflicts, population growth, loss of biodiversity.